Successful Resolution of Early-Onset Prosthetic Valve Endocarditis Associated With Extended Spectrum β-Lactamases Producing With Medical Management - Umaima Dhamrah MD; Keely Johnson MD; Aisha Amin MD; Maurice Policar MD (SAGE Publishing, 2020)
A 74-year-old male with a recent bioprosthetic mitral valve placement presented with dyspnea, chills, and palpitations. Blood cultures on admission grew extended spectrum β-lactamase Escherichia coli . Transthoracic echocardiogram and transesophageal echocardiography were negative for valvular vegetations, but given the recent history of mitral valve replacement and difficulty visualizing valvular vegetations in prosthetic valve, we initiated treatment of our patient with antibiotics for 6 weeks. Repeat blood cultures showed clearance of the organism and on follow-up, and the patient had no signs of recurrence of infection.